Structural analysis of the impact of learning from errors and organizational failures on innovative performance with the mediation role of knowledge absorptive capacity (case study: cooperative companies) - Sara Mohammadi; Farajallah Rahimi; Eslam Fakher; Ilnaz Irani Behbahani (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Learning from failures and errors is a sustainable source of knowledge for organizations, leading to an increase in employees' absorptive capacity. High ability and motivation, which are crucial factors in employees' absorptive capacity, facilitate knowledge transfer within the organization and improve organizational innovation. The main objective of this research is to examine the impact of learning from errors and organizational failures on the innovative performance of the organization, as well as to investigate the mediating role of knowledge absorptive capacity.Methodology: This study is applied in terms of its objective and descriptive-correlational in terms of data collection. The statistical population of the research includes the employees of cooperative companies in the city of Ahvaz, from which 348 individuals were selected as a non-probability accessible sample and examined. To collect the research data, standard questionnaires by Wang and Ellinger [1], Minbaeva et al. [2], Raibowick et al. [3], and Van Dyck et al. [4] were used. The validity and reliability of these questionnaires were confirmed using content validity and Cronbach's alpha (above 0.7).Findings: The results of the structural equation modeling test using SmartPLS-3 software indicated that although learning from organizational errors has a direct and significant impact on innovative performance, it also leads to a greater increase in innovative performance through employees' absorptive capacity. In other words, employees' absorptive capacity plays a facilitating and mediating role in the relationship between learning from organizational errors and innovative performance in the organization. Additionally, the results confirmed the positive and significant impact of learning from organizational errors on absorptive capacity, and absorptive capacity on innovative performance.Originality/Value: The positive impact of learning from errors on innovative performance, both directly and through absorptive capacity, showed that the company can further enhance its performance by improving absorptive capacity and gaining experience from the errors that occur within the company.